(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Inguinal hernia repair is one of the most performed surgeries worldwide. While Lichtenstein tension-free mesh repair remains the standard open technique, laparoscopic approaches such as TAPP and TEP are increasingly favored due to improved postoperative recovery and patient comfort. Aim & Objectives: To compare laparoscopic repair and Lichtenstein repair for the treatment of inguinal hernias with respect to operative outcomes, postoperative pain, complications, recovery parameters, patient satisfaction, and cost. Materials & Methods: This prospective comparative study included 100 patients with inguinal hernia, equally divided into laparoscopic (n=50) and Lichtenstein repair (n=50) groups. Outcomes assessed included operative time, complications, postoperative pain, hospital stay, return to work, patient satisfaction, and treatment cost. Statistical significance was set at p<0.05. Results: Baseline demographic characteristics were comparable between the groups. Operative time was significantly longer in the laparoscopic group (72.58±8.18 vs. 56.12±6.11 minutes; p<0.001). However, laparoscopic repair was associated with significantly lower pain scores at 24 hours, 72 hours, and 3 months (p<0.05). Hospital stay (2.12±0.48 vs. 3.63±0.70 days; p<0.001) and time to return to work (9.16±2.53 vs. 14.88±3.06 days; p<0.001) were significantly shorter following laparoscopic repair. Wound infection rates were lower (6.0% vs. 24.0%; p=0.011), while hematoma formation was slightly higher (16.0% vs. 4.0%; p=0.046). Patient satisfaction was significantly greater in the laparoscopic group (p<0.001). The mean surgical cost was higher for laparoscopic repair (₹25,149.74±2,505.40 vs. ₹4,534.30±3,418.32; p<0.001). Conclusion: Laparoscopic inguinal hernia repair offers less postoperative pain, faster recovery, a shorter hospital stay, lower wound infection rates, and greater patient satisfaction than Lichtenstein repair, though it involves a longer operative time and a higher cost.